2015
DOI: 10.1086/681971
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Writing Skills in First Grade

Abstract: We examined growth trajectories of writing and the relation of children's socio-economic status, and language and/or speech impairment to the growth trajectories. First grade children (N = 304) were assessed on their written composition in the fall, winter, and spring, and their vocabulary and literacy skills in the fall. Children's SES had a negative effect on writing quality and productivity. Children with language and/or speech impairment had lower scores than typically developing children in the quality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Overall, we found that at the end of first grade, there are measurable differences between students with below-average writing skills and those with average and strong skills. This aligns with previous research that demonstrated variability in children’s writing skills as early as kindergarten (Kim et al, 2011) and first grade (Hooper et al, 2011; Kim, Puranik, & Al Otaiba, 2015). The profiles that were found share similarities with previous work on classifying school-age writers (Hooper et al, 2006; Roid, 1994; Wakely et al, 2006); however, there are some notable differences that are discussed.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, we found that at the end of first grade, there are measurable differences between students with below-average writing skills and those with average and strong skills. This aligns with previous research that demonstrated variability in children’s writing skills as early as kindergarten (Kim et al, 2011) and first grade (Hooper et al, 2011; Kim, Puranik, & Al Otaiba, 2015). The profiles that were found share similarities with previous work on classifying school-age writers (Hooper et al, 2006; Roid, 1994; Wakely et al, 2006); however, there are some notable differences that are discussed.…”
Section: Discussionsupporting
confidence: 91%
“…A similar achievement gap is observed in children's writing skills. In first grade, children from different SES backgrounds already varied in the quality and productivity of their writing (Kim et al 2015). By the end of high school, students from low-income families scored one standard deviation lower than their peers from middle-or upper-class families in the SAT writing test (CollegeBoard 2013).…”
Section: Literacy Developmentmentioning
confidence: 99%
“…Our final two measures were the mixed nonbinary measures developed by Masterson and Apel () and used in a number of recent studies (e.g., Bailey, Arciuli, & Stancliffe, ; Clemens et al, ; Kim, Puranik, & Al Otaiba, ; McNeill, Wolter, & Gillon, ; Werfel & Krimm, ). For Spelling Sensitivity Score – Elements ( SSS‐E ), a child's spelling of a word is broken into elements, which for one‐morpheme words like those of the present study are letters or groups of letters that spell a single phoneme.…”
mentioning
confidence: 99%